Thelno Knowles - SJSU Special Collections & Archives::::::::: (2022)
Thelno Knowles attended San Jose State College from 1941-1943, and from 1946-1948 following service in World War II. He majored in Philosophy. He was a member of the campus Cosmopolitan Club, and spoke on the topic "Is This Democracy?" at the Student Center in 1943. He was a record-holding member of the track team, and competed in the AAU Championships in New York along with fellow Black student track athletes Irving Smith and Willie Steele. In 1943, Coach Bud Winter said of Knowles, "There is no man in the nation with a better chance to run a 4-minute mile." In 1945, while serving in World War II, Knowles won the European Championship at Frankfurt, Germany. During his Senior year, Knowles traveled to Los Angeles with four other track team members to compete in the invitational Coliseum Relays held by USC. In 1948, he was a captain on the SJSC varsity track team. In addition to track, Knowles took part in novice campus boxing matches. He graduated in December 1948.